(untitled) (Research, Society and Development, 2020)
Objective: To report the experience of using active methodologies by peer tutors of an undergraduate nursing course in a private higher education institution. Methods: A descriptive study, with a qualitative approach, of an experience report type, about the performance of peer tutors concerning the use of active methodologies in the nursing training process. Results: Among the results obtained, it was evident that the implementation of active methodologies was successful, as they proved to be an efficient didactic strategy, with the possibility of promoting students’ engagement, interest and motivation, collaborating for a meaningful learning. Conclusion: It is concluded that the experience of peer tutoring contributed to the applicability of active teaching methodologies with professors and students, as well as to the academic training of the tutor, providing a deeper knowledge of the subject, promoting critical-reflective thinking, interaction with the team and making them more active in their learning process.